1989
DOI: 10.1128/aac.33.8.1217
|View full text |Cite
|
Sign up to set email alerts
|

Topical delivery of liposomally encapsulated interferon evaluated in a cutaneous herpes guinea pig model

Abstract: The topical delivery of liposomally encapsulated interferon was evaluated in the cutaneous herpes simplex virus guinea pig model. Application of liposomally entrapped interferon caused a reduction of lesion scores, whereas application of interferon formulated as a solution or as an emulsion was ineffective. The method of liposomal preparation rather than the lipid composition of the bilayers appeared to be the most important factor for reducing lesion scores. Only liposomes prepared by the dehydration-rehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…Differences in the in vitro release profiles may be due to vesicle size, lamellarity, and membrane fluidity as a function of chain length of surfactant and cholesterol content (30). Table V shows that Tween 20 with cholesterol follows zero-order kinetics and the other formulations obey first- order kinetics.…”
Section: In Vitro Releasementioning
confidence: 99%
“…Differences in the in vitro release profiles may be due to vesicle size, lamellarity, and membrane fluidity as a function of chain length of surfactant and cholesterol content (30). Table V shows that Tween 20 with cholesterol follows zero-order kinetics and the other formulations obey first- order kinetics.…”
Section: In Vitro Releasementioning
confidence: 99%
“…Liposomes, small vesicles composed of phospholipids, have been used for years to bring active ingredients into the skin. Several factors such as lamellarity, lipid composition, charge on the liposomal surface, mode of application and the total lipid concentrations have been proven to influence drug deposition into the deeper skin layers (Cevc and Blume, 1992;Weiner et al, 1989). Gulasekharam (1980, 1982), Singh and Mezei (1983) and Schaeffer and Krohn (1982) were the first to report the potential use of liposomes in topical applications for the skin and eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the topical delivery of interferon (peptide drug) from liposomes was greater than that from emulsion form (w/o) or aqueous solution when in vivo applied to cutaneous herpes simplex virus guinea pig model [80]. Egbaria et al had employed a tape striping technique on guinea pig skin in vitro and liposomes showed increased deposition and accumulation of interferon into SC and deeper stratum [81]. It has been demonstrated that liposomes with lipophilic drugs such as progesterone or hydrocortisone "entrapped in the bilayer structure of the lipid vesicles" permeate the skin like the free drug itself.…”
Section: Liposomes For Transdermal Delivery Of Drugsmentioning
confidence: 99%